1984
DOI: 10.1104/pp.74.3.617
|View full text |Cite
|
Sign up to set email alerts
|

Photoinactivation of Detergent-Solubilized Plasma Membrane ATPase from Rosa damascena

Abstract: The photochemistry of vesicular and detergent-solubilized preparations of plasma membrane-associated ATPase was investigated in Rosa damascena. The cholate-solubilized ATPase activity fractionated into two peaks on a Sephadex G-150 column with simple, but different ultraviolet (UV) sensitivities. The larger enzyme was UV sensitive; the smaller enzyme was relatively insensitive. The activity of both ATPase fractions depended on environment: both were inactive in cholate, relatively inactive in phosphatidylcholi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
1

Year Published

1984
1984
2003
2003

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 12 publications
2
5
1
Order By: Relevance
“…3). This confirms a relationship previously observed between ATPase activity and tryptophan fluorescence excited at 290 nm (Imbrie and Murphy, 1984b). With the UVsensitive ATPase irradiated at 365 nm, there was proportionally a higher loss of absorption than loss of enzyme activity.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…3). This confirms a relationship previously observed between ATPase activity and tryptophan fluorescence excited at 290 nm (Imbrie and Murphy, 1984b). With the UVsensitive ATPase irradiated at 365 nm, there was proportionally a higher loss of absorption than loss of enzyme activity.…”
Section: Resultssupporting
confidence: 91%
“…The inactivation by ultraviolet light of an Mg2+requiring, K+-stimulated ATPase activity associated with the plasma membrane of suspension cultured rose cells has biphasic kinetics (Imbrie and Murphy, 1982). Using detergent-solubilized enzyme preparations fractionated on a Sephadex G-150 column, we have shown that the plasma membrane contains two distinct ATPase activities separable not only by UV sensitivity but also by molecular weight (Imbrie and Murphy, 1984a). The action spectra for inactivation of the solubilized and fractionated ATPase activities are very similar to the spectra for inactivation of ATPase in vesicles, suggesting that the proteins themselves contain the UV chromophores.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…This suggests that there is no absolute requirement for phospholipids for ATPase activity. This might seem to contradict the frequent observations that after surfactant treatment, ATPase activity can be at least partially restored by addition of phospholipids (2,8,9,17,19). Studies with other membrane-bound ATPases have shown, however, that as long as an adequate hydrophobic environment with sufficient fluidity is maintained around the ATPase, by either surfactants or lipids, activity is maintained or enhanced depending on anomalies in that environment (4,11,16,23,27).…”
Section: Discussioncontrasting
confidence: 45%
“…UV-irradiation of unwashed cells increased the specific activity of the ATPase in the plasma membranes prepared from those cells by 33%. UV clearly had effects on ATPase other than direct inactivation (such as was described for in vitro irradiation by Imbrie & Murphy (1984)), and these effects were modulated by the washing procedure.…”
Section: A Tpase Activitymentioning
confidence: 99%